Peran Supply Chain Innovation Memediasi Entrepreneur Orientation dan Innovation Performance Sektor Perikanan - Susilowati, Christin; Fakhri, Erie Awalil; Barinta, Dunga Dwi; Abanan, Muchammad Zuhri Ramadhani; Aini, Maya Faridhotul (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Alegre, J., & Chiva, R. (2013). Linking entrepreneurial orientation and organizational learning capability to innovation performance. Journal of Business Research, 9(3), 430-450. Amin, M., & Rahmawati, S. (2020). The effect of entrepreneurial orientation on innovation performance. . Asian Journal of Innovation and Policy, 3(1), 3-18. Bai, C. R., J. . (2016). Exploring the relationship between supply chain collaboration and innovation capabilities. Journal of Business Logistics, 37(2), 116-131. Barreto, L. S. (2024). Measuring innovation performance in small and medium enterprises: A unidimensional approach. Journal of Innovation Management, 21(3), 317-343. Carter, S. (2023). Entrepreneurial behaviors and innovation in small businesses. Small Business Economics, 45(4), 23-38. Cuthbertson, R. F., P. I. (2022). Supply chain innovations and firm performance: The moderating role of industry dynamism. Industrial Marketing Management, 8(2), 25-37. Gao, T., Tang, X., Wang, X., & Chen, L. (2017). Supply chain innovation and performance: Evidence from Chinese manufacturing firms. International Journal of Operations & Production Management, 37(10), 1457-1474. Ghobadi, S. (2023). The role of entrepreneurial orientation in organizational resilience. Journal of Entrepreneurship Research, 35(2), 145-162. Hilmersson, M. (2014). The effects of entrepreneurial orientation on firm performance. Entrepreneurship Research Journal, 4(2), 167-190. Malacina, R. T., A. (2022). Innovations in supply chain systems: Drivers and challenges. Operations and Supply Chain Management Journal, 15(3), 51-62. Mingyue Fan, Q., Wang, X., & Liu, S. (2021). Entrepreneurial orientation and SME innovation performance. Journal of Small Business Management, 59(4), 134-152. Mittal, S., Khan, M. A., Romero, D., & Wuest, T. (2018). A critical review of smart manufacturing & Industry 4.0 maturity models: Implications for SMEs. Journal of Manufacturing Systems, 49(1), 194-214. Müller, R., Pemsel, S., & Shao, J. . (2021). Supply chain integration and Industry 4.0: Impacts on innovation and firm performance. Journal of Cleaner Production, 34(2), 256-270. Ndubisi, N. O. I., K. (2012). Relationship between entrepreneurial orientation, innovation, and firm performance. Journal of Business Research, 65(4), 673-678. Purnomo, H., Kusumaningtyas, N., & Nugroho, A. (2022). Exploring the role of entrepreneurial orientation in SMEs innovation. International Journal of Innovation, Creativity, and Change, 17(2), 45-58. Putra, A. A. (2021). Pengaruh Integrasi Supply Chain (Sci) Terhadap Kinerja Operasional Umkm Di Kabupaten Bantul. Rosenbusch, N., Brinckmann, J., & Bausch, A. (2011). Is innovation always beneficial? A meta-analysis of the relationship between innovation and performance in SMEs. Journal of Business Venturing, 26(4), 761-787. Sarsah, S. A., Boafo, A. J., & Kwesi, B. (2020). Entrepreneurial orientation and innovation performance in emerging markets. International Business Research, 13(3), 12-25. Tajeddini, K., Ratten, V., & Denisa, M. (2020). Revisiting the relationship between entrepreneurial orientation and innovation performance in SMEs. Journal of Small Business Economics, 39(5), 945-962. Tambunan, T. (2019). Development of SMEs in ASEAN with a focus on Indonesia. Journal of Southeast Asian Economies, 38(3). Wang, Y., Zhang, S., & Liu, Y. (2017). The role of entrepreneurial orientation in dynamic business environments. Journal of Business Strategy, 38(3), 49-57. Wong, W., Tan, F., & Lee, K. (2016). Assessing the impact of supply chain innovation on performance: Evidence from SMEs. Journal of Supply Chain Management, 47(3), 89-105.